OCCUPATIONAL STRUCTURE OF POVERTY - Tünde-Ilona KELE (Annals of the University of Oradea: Economic Science)
The main objective of this paper is to present the relationship between poverty, unemployment and education reaching the occupational structure of poverty. In order to understand the interdependence of the three concepts, I have started with the review of the definitions given by renowned specialists in the study of poverty. Afterwards, I have analysed the causes, determinants and types of poverty. Subsequently, I have brought in the foreground the statistical data regarding the Romanian population in the period between 2018 and 2021, which reflect the extent to which the citizens of our country are exposed and especially the children of the scourge of poverty. I wanted to highlight the interdependence between the level of education, unemployment and poverty rate. I have reviewed the ongoing plans and strategies undertaken by the Romanian Government having as objective the eradication of poverty by ensuring a quality education, which is considered an effective instrument for breaking the vicious circle of poverty.